Students' perception of EdD and PhD programmes in Hong Kong. Issue 4 (2nd October 2018) - Jung, Jisun
Abstract: The aim of this study is to explore the learning experiences of students enrolled on a Doctorate in Education programme in Hong Kong. The main questions are as follows. How do EdD students position themselves as doctoral candidates? How do EdD students experience their education in terms of scholarly expertise and scholarly identity? How do EdD students characterise their relationships with their supervisors? What perceptions do PhD students hold of the field of knowledge of EdD students and the value of an EdD degree? The data obtained from 10 semi-structured interviews in one selected institution are discussed with reference to the four main themes; distinction between EdD and PhD degrees: 'co-existent' vs. 'separate'; positioning of EdD programme: title of doctor as 'unfair' vs. 'deserved'; scholarly value: 'insightful' vs. 'non-academic'; and relationship with supervisor: 'independent and self-managed' vs. 'never equal, unlike the relationship between PhD student and supervisor'.